The Influence of Relationship Marketing on Loyalty with Mediation of Customer Trust at PT. Bank Rakyat Indonesia (Persero) Tbk Krian Branch Office - Faizal Riza; Rahmat Agus Santoso (Dinasti International Journal of Economics, Finance & Accounting, 2023)
The banking industry currently needs to have the right strategy to grow and retain customers so they can continue to use the banking services provided. This is because competition in the banking industry in the digitalization era is getting tighter and more competitive. Loyalty to customers is one of the main considerations for advancing the core business of the banking industry. because loyal customers will always continue to use the services that the bank will provide, so it is very important for businesses to encourage customers to continue to support them. The potential to increase loyal customers is by paying attention to Relationship Marketing which in the study in the study identified trust as a mediating variable. This research approach uses a quantitative approach, using 110 respondents who meet the requirements. Data analysis technique using Partial Least Square (PLS) Structural Equation Modeling (SEM) analysis, the hypothesis in this study is Allegedly there is an influence of Relationship Marketing which has a significant effect on Customer Loyalty, Allegedly Relationship Marketing has a Significant effect on Trust, Allegedly Trust has a Significant effect on Customer Loyalty, it is suspected that Relationship Marketing has a significant effect on Loyalty through Trust mediation. Based on the analysis results show that all hypotheses in this study can be accepted. Therefore, this may be a strategy that can provide an advantage for future businesses in the area. The company's management should acknowledge the results of the analysis in this paper. Based on the results of the analysis, relationship marketing, whether carried out slowly or quickly with a focus on customer loyalty or through the use of trust-building media, will provide significant benefits. As a result, the more management understands relationship marketing and customer loyalty, the more favorable situation for customer loyalty at BRI Krian Branch Offices.